MODEL MATEMATIKA DINAMIKA HARGA CRYPTOCURRENCY - Yonesa, Salsabila; Subhan, Muhammad (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2024)
Current technological developments have digital money or cryptocurrency which is currently being used as an investment by the world community. here are views about cryptocurrencies, there is a profitable opportunity by involving cryptocurrencies into the economy and monetary system. The aim of this research is to form a cryptocurrency price dynamics model, analyze the stability of the equilibrium point and interpret the results of the model simulation. This type of research is basic or theoretical research. The method used is a descriptive method. This dynamic model takes the form of a system of differential equations consisting of five equations. In the analysis of the dynamic model, it was found that one equilibrium point was unstable because it did not meet the requirements. Based on the analysis of the simulation results that have been carried out, it shows that cryptocurrency prices deviate from fundamental values with the encouragement of liquidity prices resulting in cryptocurrency prices deviating from the equilibrium point